3D stratigraphic mapping and reservoir architecture of the Balakhany Suite, Upper Productive Series, using UAV photogrammetry: Yasamal Valley, Azerbaijan. (November 2022) - Shahtakhtinskiy, Aydin; Khan, Shuhab
Abstract: Developments in digital outcrop geology have facilitated the stratigraphic, structural, and sedimentologic characterization of outcrop analogs for applications in the petroleum industry. Here, unmanned aerial vehicles (UAVs) and Structure from Motion photogrammetry have been used to create a digital outcrop model of the Upper Productive Series clastic succession in Yasamal Valley, Apsheron Peninsula, that serves as a valuable analog to hydrocarbon-rich Pliocene reservoirs of the South Caspian Basin. The UAVs provided an advantageous perspective on the low-gradient exposures along the depositional strike and allowed stratigraphic mapping in a 0.1 km 2 area, which was previously difficult to image in the field using conventional methods. Petrographic and mineralogical analyses of outcrop samples were also used to identify facies types. Key stratigraphic surfaces and depositional elements within the channelized succession were mapped with the aid of surface attributes to produce a high-resolution facies architecture and evaluate reservoir heterogeneity of the low to intermediate net-to-gross Balakhany Formation. The interpreted framework shows a range of reservoir types deposited in a prograding delta front setting, represented by an increase in sandstone-body proportions and degree of channelization within a coarsening-upward succession. Channel-body dimensions were measured and categorized based on published global datasets. Sandstone proportions were quantified, and rapid lateral and vertical variations in net-to-gross were revealed. This study provides useful information for correlation of wells and modeling of heterogeneous, low to moderate net-to-gross reservoirs of the offshore fields in the South Caspian Basin. Highlights: Digital outcrop models allowed to reveal a unique depositional strike-oriented stratigraphic architecture of a low-angle clastic succession. New insights on depositional style are provided and a deltaic depositional model is proposed. Mapping of key surfaces and depositional elements suggests a highly heterogenous, low to intermediate net-to-gross reservoir architecture. A range of reservoir types and baffles/barriers to fluid flow should be incorporated to improve geological models of analog fields.